Investigation of the Ternary Blended Self-Compacting Concrete with Fiber’s Strength and Durability Properties - Priyan, Pawar; Rama Prasad, C. Venkata Siva; Reddy, B. Sudharshan (Journal of Neonatal Surgery, 2025)
This study investigates the effect of ternary blended self-compacting concrete (SCC) mixes incorporating fly ash and silica fume on the compressive strength, splitting tensile strength, flexural strength, and modulus of elasticity over different curing periods (7, 14, 28, and 56 days). The results revealed that the compressive strength increased with up to 20% fly ash substitution, with an optimal improvement of 13.64% at 28 and 56 days in the mix with 20% fly ash and 10% silica fume (TBC9). Similarly, splitting tensile strength and flexural strength exhibited significant improvements in mixes TBC9 and TBC10, particularly at 28 and 56 days, while the addition of glass fibers further enhanced tensile strength. The modulus of elasticity showed an increase in stiffness, with TBC9 demonstrating the highest value at 31.04 GPa. The study emphasizes the potential of ternary blends with fly ash and silica fume in enhancing the mechanical and physical properties of SCC, particularly with 20% fly ash and 10% silica fume